Pelatihan Mengajar Dan Menulis Laporan Hasil Belajar Dalam Bahasa Inggris Untuk Guru SMP/SMA Tumbuh Yogyakarta - Adaninggar Septi Subekti; Arida Susyetina (LPPM UMRI, 2019)
Abstract This community service activity aims to provide English language training for teachers of Tumbuh High School, Yogyakarta, Indonesia. This training focuses on English for classroom use and student report writing. The training was conducted by two facilitators (the authors) in ten meetings. The main activities, six face-to-face in-class sessions, included syllabus presentations, discussions about teaching styles, sharing of teaching experiences and of various needs to meet especially to facilitate or accommodate some students with special needs, teaching demonstrations, and report writing. All of these activities were conducted in full English. Follow-up activities were in the form of one facilitators-participants conference in which the facilitators met each participant individually and discussed his/her progress in learning, two class observations in which the facilitators observed the participants teaching in their respective classes, and one discussion session with the curriculum coordinator about the progress of the participants during the training as an input for the school to determine the follow-up policy regarding the participants’ professional development.